2019
DOI: 10.3390/vaccines7040151
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Whole-Cell Pneumococcal Vaccine

Abstract: Streptococcus pneumoniae remains a major public health hazard. Although Pneumococcal Conjugate Vaccines (PCVs) are available and have significantly reduced the rate of invasive pneumococcal diseases, there is still a need for new vaccines with unlimited serotype coverage, long-lasting protection, and lower cost to be developed. One of the most promising candidates is the Whole-Cell Pneumococcal Vaccine (WCV). The new generation of whole-cell vaccines is based on an unencapsulated serotype that allows the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…37 For the future, serotype independent vaccines may help combat invasive pneumococcal infections. 38 Our observation of lower ESBL rates in E. coli isolates from children than from adults is comparable with studies from North America, 12,39 and the lower resistance rate to ciprofloxacin is even more dominant in other reports. 8,12 In Canada, gentamicin resistance in isolates from children was reported lower than in adults, 12 while a European study reported the opposite.…”
Section: Discussionsupporting
confidence: 90%
“…37 For the future, serotype independent vaccines may help combat invasive pneumococcal infections. 38 Our observation of lower ESBL rates in E. coli isolates from children than from adults is comparable with studies from North America, 12,39 and the lower resistance rate to ciprofloxacin is even more dominant in other reports. 8,12 In Canada, gentamicin resistance in isolates from children was reported lower than in adults, 12 while a European study reported the opposite.…”
Section: Discussionsupporting
confidence: 90%
“…It is established that virulence factors, as important components of bacteria, can be alternative vaccine antigens. Recent report proved that conserved proteins that have been proposed for candidate vaccines should possess favorable immunogenicity and immunoreactivity of antigen, such as pspA, inhibiting the activation of the C3 complement protein and elevating the colonization ability of S. Pneumoniae [27] .…”
Section: Virulence Genes Distribution and Patternmentioning
confidence: 99%
“…Pneumolysin (Ply) is a cytotoxic cholesterol-binding protein, which is released during autolysis of bacteria that can form pores in eukaryotic membranes [65,66]. Besides its lytic activity, Ply is able to activate complement and the innate immune system through the toll-like receptor-4 (TLR4) and NOD-, LRR-and pyrin domain-containing protein 3 (NLRP3) inflammasome [80][81][82]. Activation of complement by Ply is known to cause complement depletion and reduces complement binding to pneumococcus.…”
Section: Protein-based Vaccinesmentioning
confidence: 99%